(untitled) (Research, Society and Development, 2022)
Endodontic treatment aims to prevent or treat periapical changes resulting from pulp injuries. In immature permanent teeth the treatment has some peculiarities. Among the treatment modalities used in these cases is regenerative therapy. This is an option for the treatment of necrotic teeth with open apex, being an alternative to apexification that is performed worldwide with great success, but does not allow the end of tooth development, often leaving the walls fragile and thin, susceptible to fractures and consequent loss. of the dental element. In addition, she needs several sessions for periodic exchanges of calcium hydroxide; having a greater risk of new contamination inside the root canal. Patient collaboration can become a negative factor due to the successive necessary consultations. With the evolution of science and new research carried out, regenerative therapy can be an advantageous replacement for apexification, as it is faster and with promising results, however, further studies are needed to improve the technique, develop a definitive protocol, as well as studies of the results achieved in the long term. This paper is intended to present a clinical case of regenerative therapy of a necrotic tooth and open apex with a diagnosis of pulp necrosis of an maxillary left central incisor of an 8-year-old child after previous trauma.